Tax Treatment Analysis of Supply Chain and Distributor Transactions at a Nestlé Distributor Company in Manokwari Regency - Christine Sada Meyranda Marpaung; Devy Monica Toding; Arif Wiratama Fattah; Obeloni Mandacan (Green Publisher Indonesia, 2026)
This study examines the tax treatment of supply chain transactions involving distributor incentives in a Nestlé distributor company in Manokwari Regency. In modern trading practices, manufacturers frequently provide rewards such as bonuses, discounts, cashback, free goods, and service fees to stimulate sales performance. However, these incentives often create complexity in accounting recognition and taxation, particularly for distributors acting as intermediaries. This study aims to analyze how such reward transactions should be properly recorded and treated for taxation purposes in accordance with Indonesian tax regulations. The research employed a qualitative descriptive approach using primary data collected through participant observation, in-depth discussions, and documentation of financial and tax records at CV Aditya Citra Persada. The findings indicate that different forms of rewards generate distinct tax consequences, including obligations related to Income Tax Article 23, final income tax, and Value Added Tax (VAT). The study also reveals that prior misclassification of reward transactions as deposits led to inaccuracies in tax reporting, while improved recognition as income has enhanced compliance and reporting accuracy. In conclusion, proper alignment between accounting treatment and tax regulations is essential to ensure compliance and minimize fiscal risks. Distributors must adopt accurate transaction recording and clear contractual arrangements to support consistent and lawful tax reporting practices.